A new species of Raphidopus Stimpson, 1858, from the Persian Gulf (Crustacea: Decapoda: Anomura: Porcellanidae) - Ng, Peter K. L.; Safaie, Mohsen; Naser, Murtada D. (Zootaxa, 2012)
A new species of porcellanid crab, Raphidopus persicus, is described from Iran and Iraq in the Persian Gulf. The speciesis distinguished from its congeners, R. ciliatus Stimpson, 1858, R. indicus Henderson, 1893, and R. johnsoni Ng & Naka-sone, 1994, by a combination of carapace features, structure of the third maxilliped and thoracic sternum, cheliped armature, and proportions of the ambulatory legs.